The Epilepsy Drug Pipeline: Update on Near-to-Market Therapies - Elder, Christopher; Pellinen, Jacob; Terman, Samuel W. (Seminars in Neurology, 2025)
Since the first antiseizure medication (ASM) was introduced in 1857, more than 30 medications have been approved by the United States Food and Drug Administration (FDA) for the treatment of epilepsy. However, limitations in efficacy and tolerability have led to one-third of patients suffering from uncontrolled seizures. Recent advances in genetics, disease modeling, high-throughput target-based and phenotype-based screening, study design, and identification of novel mechanisms of action or routes of delivery have resulted in more than 200 therapeutics currently under development in the epilepsy pipeline. This study discusses near-to-market drugs in advanced clinical development, with select drugs in earlier stages. Background regarding mechanisms, animal studies, pharmacokinetics, pharmacodynamics, efficacy, tolerability, and safety data are provided for each drug when available.
Keywords: epilepsy; antiseizure medications; clinical trials; pipeline